1993
DOI: 10.1289/ehp.9310150
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between chemically related site-specific carcinogenic effects in long-term studies in rats and mice.

Abstract: We examined a database of 379 long-term carcinogenicity studies in rats and mice to evaluate sex and species correlations in site-specific carcinogenic responses. Within a species, most target sites showed a strong correlation between males and females. For example, chemicals producing forestomach or liver tumors in males were likely to produce these same types of tumors in females. There was also a significant correlation between species for certain site-specific carcinogenic effects, most notably tumors of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Moreover, the species specificity was remarkably higher than the sex specificity among different species. This result is in agreement with evidence found by other investigators in different subsets of the database(17,18).A similar check was performed on the potency data. For this preliminary analysis, we used the TD50 values listed by species/sex group in a compilation byNesnow (19).…”
supporting
confidence: 92%
“…Moreover, the species specificity was remarkably higher than the sex specificity among different species. This result is in agreement with evidence found by other investigators in different subsets of the database(17,18).A similar check was performed on the potency data. For this preliminary analysis, we used the TD50 values listed by species/sex group in a compilation byNesnow (19).…”
supporting
confidence: 92%
“…Thus, based on the results from testing a chemical with 50 animals per group, the probability of at least one tissue site with a statistically dose-response trend can be estimated for a chemical with a specified larger sample size, e.g., 200 animals per group. Haseman and Lockhart (1993) indicate relatively few correlations between chemically related site-specific carcinogenic effects.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18][19] Only two epidemiology studies of AMD-exposed workers have been conducted to date. Recognizing the limitations of extrapolating findings of carcinogenicity bioassays across animal species or from animals to humans, 20 these studies were prompted by experimental animal studies that suggested AMD's carcinogenic potential based on an increased incidence of cancers, including those of the brain and other central nervous system (CNS), thyroid gland, other endocrine glands, reproductive organs, and mesotheliomas. [3][4][5][6] The first epidemiology study, a small historical cohort study of 371 Dow Chemical Company employees assigned to AMD monomer and polymerization operations, found no statistically significant mortality excesses in the total cohort and no deaths for the implicated cancer sites.…”
mentioning
confidence: 99%